Penerapan Model Cooperative Learning Tipe Jigsaw dalam Meningkatkan Hasil Belajar Tematik Siswa Kelas III SDN Sumur Welut I Surabaya - Nabila Syaputri; Muhammad Sukron Djazilan; Sri Hartatik; Dewi Widiana Rahayu (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The background of this research is the low student learning outcomes and the low cooperative attitude of students which has an impact on low student learning outcomes in thematic learning. The purpose of this study is to describe the application and improvement of the jigsaw cooperative learning model. This research method uses Classroom Action Research with the Kurt Lewin Model. The subjects of this study were 22 class III students at Sumur Welut I Elementary School, 9 male students and 11 female students. The study was conducted in 2 cycles, each cycle experiencing an increase in learning outcomes. Cycle I thematic learning student learning outcomes obtained an average score of 76.67 with a completeness percentage of 59%. In cycle II the thematic learning outcomes of students obtained an average score of 91.25 with a completeness percentage of 91%. Based on these results, the Jigsaw cooperative learning model can improve the learning outcomes of third grade elementary school students.